Carbon Bed Interflow Performance Prediction Using Variable Hypothetic Pressure Wave Cycles Model - Yusep K Caryana (Testing Center for Oil and Gas LEMIGAS, 2009)
The nature of low productivity of CBM well experiences represent low interflow performace over matrix and fractures in coal bed. Therefore, to increase CBM well production rate, it is necessary to improve the interflow performace. An approach to improve the interflow performance is to find out the possibility of increasing gas flowrate in carbon bed taken into account factors dominantly effect on the performance. For this purposes, Variable Pressure Wave Cycles Hypothetical Model has been developed based on Pressure-Swing adsorption - desorption (PSA) technique commonly applies in natural gas separation using carbon active bed. Preliminary simulation of the model has been carried out using data related to carbon bed taken from previous studies. Variables in the simulation are kinetic constant and hypothetic pressure waves generated which is required to increase gas flow rate in the bed. The simulation results demonstrate the possibility of interflow performance improvement in carbon bed. However, this improvement is asymptotically limited to maximum amount of gas desorbed from carbon bed as well as Langmuir Isotherm pattern application for gas desorption from coal. Moreover, the simulation of the model shows the sensitivity of gas interflow performance to hypothetical pressure waves generated and kinetics controlling adsorption/desorption mechanism and mass transport in carbon bed.